2008
DOI: 10.1345/aph.1k679
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Floppy Iris Syndrome Associated with α1-Adrenergic Receptor Antagonists

Abstract: IFIS is a clinical syndrome observed during cataract surgery reported in patients taking systemic alpha(1)AR antagonists. It has been most strongly linked to use of tamsulosin. Medication washout periods of up to 2 weeks and specific surgical procedures have been attempted to reduce risk of complications from alpha(1)AR antagonists in the setting of cataract surgery. Patients should be educated regarding potential risks of this drug class so that they can discuss them with their healthcare providers, specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 26 publications
0
27
0
3
Order By: Relevance
“…Subsequent reports, similar to our own, have shown that terazosin, doxazosin and alfuzosin can be related to IFIS. 16,17 It is likely that the entire class of alpha-blockers can cause IFIS. However, the syndrome seems to be less common and less severe with others as compared to when tamsulosin is used.…”
Section: Ifismentioning
confidence: 99%
“…Subsequent reports, similar to our own, have shown that terazosin, doxazosin and alfuzosin can be related to IFIS. 16,17 It is likely that the entire class of alpha-blockers can cause IFIS. However, the syndrome seems to be less common and less severe with others as compared to when tamsulosin is used.…”
Section: Ifismentioning
confidence: 99%
“…The increased 1A AR selectivity of the third-generation "uroselective" agents tamsulosin and silodosin is postulated to provide additional relief of LUTS in patients with BPH without increasing the rate of serious adverse cardiovascular effects due to systemic AR antagonism. (Cantrell et al, 2008;Cantrell et al, 2010) 1 AR antagonists not only therapeutically inhibit prostatic 1 AR but may also selectively antagonize these receptors in the iris dilator muscle. In the iris, 1A AR mediate iris dilator smooth muscle contraction whereas iris arteriolar contraction is mediated via 1B AR.…”
Section: Pathophysiology Of Ifismentioning
confidence: 99%
“…Tamsulosin is the most antagonists. Tamsulosin is the most Tamsulosin is the most uroselective alpha-1AAR antagonist approved for use alpha-1AAR antagonist approved for use antagonist approved for use in the treatment of symptomatic BPH, which, although it improves urinary outflow, is also thought to inhibit the iris dilator smooth muscles causing varying degrees of IFIS (7)(8)(9). The effectiveness of tamsulosin is similar to other alpha-1AAR blocker drugs.…”
Section: Bph-ifis and Adrenergic Receptorsmentioning
confidence: 99%
“…This may relate to differences in receptor affinity with tamsulosin and with other related medications. It is believed that tamsulosin is more highly selective for alpha-1AAR antagonists than alpha-1AAR antagonists than antagonists than other alpha-1AAR blocker drugs (8). These particular alpha-1AAR blocker drugs (8).…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation